CEKAT E-JKN Service (Quick, Effective, and Accurate) at Pandanwangi Urban Village, Blimbing Subdistrict, Malang City - Lestari, Asih Widi; Lestari, Dewi Citra; Citra, Honorata (GEMA PUBLICA, 2025)
Public services are services that can be provided in a country to fulfill the basic needs and rights of citizens. Health is a basic human need and a top priority in life. As the person responsible for health services, the state has a responsibility to improve the welfare of all people. Based on Presidential Decree of the Republic of Indonesia Number 82 of 2018, it is stipulated that registration for national health insurance is divided into two parts, namely participants who receive contribution assistance (PBI) and participants who do not receive it. Recipients of Contribution Assistance (PBI) Contributions (Non-PBI). PBI participants are people who are classified as poor or disadvantaged, registered by the government and identified by the Ministry of Social Affairs. This research uses a qualitative approach. Data collection was carried out through interviews, observation and documentation. Data analysis uses the Miles and Huberman interactive model which consists of data reduction, data presentation, and drawing conclusions. The results of this research show that there are procedures or procedures for applying for e-JKN Cekat, you can apply for BPJS Mandiri to KIS-PBI, BPJS Mandiri/KIS people who have become inactive become active again (urgent), re-check BPJS membership data/ KIS through the WahtsApp CHIKA Application, the existence of the Cekat e-JKN Website, the reliability of employees in providing Cekat e-JKN services, the responsiveness and care of employees who have the ability to help the community to increase the speed of Cekat e-JKN services, guarantees of certainty that must be instilled in the community as much as possible possible, providing the best possible service to the community, evidence of real action by employees in conveying directions to the community, communicating politely, being responsible and paying attention to the rights and obligations of the community who want to take care of KIS, and attention in providing direction regarding the requirements for applying for e-JKN Cekat. The supporting factor in Cekat e-JKN services is the existence of a budget from the Malang city government in the form of KIS APBD, facilities and infrastructure (Computer, WIFI and Chika), while the inhibiting factor in Cekat e-JKN services is the absence of an SOP regarding the flow of e-JKN applications. Cekat, and the community concerned did not appear in person to apply for Cekat e-JKN.